POSTKOLONIALISME DALAM ANTOLOGI CERPEN SEMUA UNTUK HINDIA KARYA IKSAKA BANU: KAJIAN TEORI HOMI K. BHABHA - Ratnasari, Andaru; Mardiah Wahab, Wilda; Muhri, Muhri (Universitas Hamzanwadi, 2024)
The study aims to describe and explain the form of postcolonialism in the short story anthology Semua untuk Hindia by Iksaka Banu using Homi K. Bhabha's thoughts, namely: (1) mimicry and humans, (2) signs taken for miracles, and (3) ancient articulation. This study uses a qualitative descriptive method. The data source in this study comes from the short story anthology by Iksaka Banu Semua untuk Hindia. The results of the postcolonialism research of the anthology are based on the dominant order related to the conditions of postcoloniality, namely the strong issue of ambivalence, then followed by mimicry, and finally hybridity. Postcolonialism as a condition and impact of colonialism is strongly attached to the short story anthology Semua untuk Hindia feels dominant because it contains an ambivalent narrative starting from the story of the pre-arrival period of the Dutch East Indies to Indonesian independence.